Effects of assessing the bone remodeling process in biomechanical finite element stability evaluations of dental implants. (June 2022) - Park, Soyeon; Park, Jieun; Kang, Inyeong; Lee, Hyeonjong; Noh, Gunwoo
Highlights: The effects of assessing the bone remodeling process in the FE analysis were investigated Total six short dental implant systems of various implant diameters and bone qualities were evaluated With bone remodeling, bone quality affects the FE analysis more than the implant diameter The FE analysis without the bone remodeling process could underestimate the risks for elderly patients Abstract: Background and objective: While an accurate assessment of the biomechanical stability of implants is essential in dental prosthesis planning and associated treatment assurance, the bone remodeling process is often ignored in biomechanical studies using finite element (FE) analysis. In this study, we aimed to analyze the significance of assessing the bone remodeling process in FE analysis for evaluating the biomechanical stability of dental implants. We compared the FE results considering the bone remodeling process with FE results simulated using commonly used conditions, with no considerations of the bone remodeling process. Methods: The mathematical model proposed by Komarova et al. was used to calculate cell population dynamics and changes in bone density at a discrete site. The model was implemented in the FE software ABAQUS, using the UMAT subroutine. Three-dimensional FE models were constructed for two types of bone (III and IV) and three values of implant diameter (4.0, 4.5, and 5.0 mm). An average biting force of 50 N in the vertical direction was applied during the bone remodeling process for 150 days. Afterwards, the maximum biting force of 200 N in the 30° oblique direction was applied to evaluate the stability of the implant systems. Results: To understand the impact of bone remodeling on the resultant mechanical responses, we focused on peri-implant cancellous bone based on two parameters: apparent density change and microstrain distribution. The bone density decreased by an average of 5.3 % after implantation, and it was the lowest on the 6 th day. The average density increases of the peri-implant cancellous bone were 264.4 k g m 3 (bone type III) and 220.0 k g m 3 (bone type IV) over 150 days. For the bone stability analysis, the maximum principal strain in the peri-implant bone was used to evaluate the bone stability. If the bone remodeling process is ignored, then the bone volume within the fatigue failure range of the microstrain differs significantly from that if the bone remodeling process is considered, i.e., 60 % higher for bone type III and 33.4 % lower for bone type IV than when the bone remodeling process is considered. Conclusions: The FE result without considering the bone remodeling process could be considered a conservative criterion for bone type III. However, in bone type IV, the FE result without considering the bone remodeling process tends to underestimate the risks. The bone remodeling process is more affected by the initial bone quality than the implant diameter.